Eksistensi Fiqh Dalam Konteks Siyasah Kekinian: Studi Kasus Penerapan Qanun Nomor 6 Tahun 2014 Tentang Hukum Jinayat Di Aceh - Muhammad Muhammad (Ma'had Aly Raudhatul Ma'arif, 2023)
The enactment of Law No. 18/2001 granted the Aceh government special autonomy, enabling it to implement Sharia principles through the drafting of Qanuns grounded in Fiqh. This autonomy distinguishes Aceh as a region where Islamic law is uniquely integrated into modern governance. One significant example is Qanun No. 6 of 2014 on Jinayat Law, which regulates criminal acts based on Sharia principles. This study examines the role of Fiqh in shaping and applying this Qanun, focusing on two main questions: how Fiqh is represented in Qanun No. 6 of 2014 and whether its implementation aligns with Fiqh principles. Employing a qualitative approach and library research methods, the study draws on primary sources such as legal texts and books, supplemented by academic journals and related studies. The findings reveal that the Jinayat Qanun incorporates key Fiqh principles, reflecting Aceh’s commitment to upholding Islamic law. Legal provisions and punishments within the Qanun are primarily aligned with classical Fiqh guidelines. However, certain aspects deviate or fall short of fully adhering to Fiqh norms due to challenges in adapting traditional jurisprudence to contemporary legal and societal contexts. In conclusion, the study highlights the significance of Islamic law in Aceh’s governance, emphasizing its strengths and identifying areas for improvement. The implementation of Qanun No. 6 of 2014 illustrates the dynamic interplay between Fiqh and local governance, positioning Aceh as a unique example of contemporary siyasah rooted in Islamic principles.